PENGARUH MEDIA JAM DINDING TERHADAP KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA SISWA KELAS III - Salsabila, Nur; Mardiana, Mardiana; Septiadi, Wahyu (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This study was motivated by the low level of students’ enthusiasm in participating in conventional mathematics learning, which has impacted their ability to solve word problems. The purpose of this research was to determine the effect of using a “wall clock” learning media on students’ ability to solve word problems in the topic of time measurement for third-grade students at SD Negeri 28 Kelakik. The study employed a quantitative approach with a pretest–posttest control group design. Data were collected through tests administered before and after the treatment, as well as classroom observations during the learning process. The experimental group received instruction using wall clock media as a visual aid to facilitate understanding of time measurement concepts in daily life, while the control group was taught using conventional methods. The results indicated an increase in the average scores of the experimental group from pretest to posttest. Hypothesis testing showed a significance value of 0.008 (α < 0.05), indicating that the use of wall clock media had a significant effect on students’ ability to solve word problems. Therefore, wall clock media can serve as an alternative instructional tool to support improved mathematics learning outcomes in elementary schools.